Preliminary Results of Implantation in Animal Model and Osteoblast Culture Evaluation of Prototypes of Biomimetic Multispiked Connecting Scaffold for Noncemented Stemless Resurfacing Hip Arthroplasty Endoprostheses. (29th July 2013) - Uklejewski, Ryszard; Rogala, Piotr; Winiecki, Mariusz; Kędzia, Andrzej; Ruszkowski, Piotr
Abstract : We present the new fixation method for RHA (resurfacing hip arthroplasty) endoprostheses by means of the biomimetic multispiked connecting scaffold (MSC-Scaffold). Such connecting scaffold can generate new type of RHA endoprostheses, that is stemless and fixed entirely without cement. The preprototypes of this MSC-Scaffold were manufactured with modern additive laser additive technology (SLM). The pilot surgical implantations in animal model (two laboratory swine) of MSC-Scaffold preprototypes have showed after two months neither implant loosening, migration, and nor other early complications. From the results of performed histopathological evaluation of the periscaffold spikes bone tissue and 10-day culture of human osteoblasts (NHOst) we can conclude that (1) the scaffolding effect was obtained and (2) to improve the osseointegration of the scaffold spikes, their material surface should be physicochemically modified (e.g., with hydroxyapatite). Some histopathological findings in the periscaffold domain near the MSC-Scaffold spikes bases (fibrous connective tissue and metallic particles near the MSC-Scaffold spikes bases edges) prompt considering the necessity to optimize the design of the MSC-Scaffold in the regions of its interspike space near the spikes bases edges, to provide more room for new bone formation in this region and for indispensable post-processing (glass pearl blasting) after the SLM manufacturing.